St. Patrick's Day in the morning - Bunting, Eve, 1928-; Brett, Jan, 1949- (New York : Houghton Mifflin/Clarion Books, 1980)
Jamie seeks a way to prove he is not too young to march in the big St. Patrick's Day parade.
Booklist
School Library Journal
Kirkus Reviews
2.0
K-3
Keywords: Saint Patrick's Day -- Fiction; St. Patrick's Day -- Fiction; Parades -- Fiction